Multidrug-Resistant (MDR) Urinary Tract Infections Associated with Gut Microbiota in CoV and Non-CoV Patients in a Urological Clinic during the Pandemic: A Single Center Experience - Viorel Dragos Radu; Radu Cristian Costache; Pavel Onofrei; Egidia Miftode; Iacov Linga; Radu Mihaita Ouatu; Lucian Boiculese; Razvan Lucian Bobeica; Ingrid Tanasa Vasilache; Irina Luanda Mititiuc (MDPI AG, 2023)
The aim of the study was to compare the profile of COVID-19 (CoV)-infected patients with non-COVID-19 (non-CoV) patients who presented with a multidrug-resistant urinary tract infection (MDR UTI) associated with gut microbiota, as well as analyze the risk factors for their occurrence, the types of bacteria involved, and their spectrum of sensitivity. Methods: We conducted a case-control study on patients admitted to the urology clinic of the "Parhon" Teaching Hospital in Iasi, Romania, between March 2020 and August 2022. The study group consisted of 22 CoV patients with MDR urinary infections associated with gut microbiota. For the control group, 66 non-CoV patients who developed MDR urinary infections associated with gut microbiota were selected. Electronic medical records were analyzed to determine demographics, characteristics, and risk factors. The types of urinary tract bacteria involved in the occurrence of MDR urinary infections and their sensitivity spectrum were also analyzed. Results: Patients in both groups studied were over 60 years of age, with no differences in gender, environment of origin, and rate of comorbidities. Patients in the CoV group had a higher percentage of urosepsis (54.5% versus 21.2%, p < 0.05) and more hospitalization days (9.27 versus 6.09, p < 0.05). Regarding risk factors, the two groups had similar percentages of previous urologic interventions (95.45% versus 96.97%, p > 0.05), antibiotic therapy (77.3% versus 87.9%, p > 0.05), and the presence of permanent urinary catheters (77.27% versus 84.85%, p > 0.05). Escherichia coli (31.8% versus 42.4%, p > 0.05), Klebsiella spp. (22.7% versus 34.8%, p > 0.05), and Pseudomonas aeruginosa (27.3% versus 9.1%, p > 0.05) were the most common urinary tract bacteria found in the etiology of MDR urinary infections in CoV and non-CoV patients. A high percentage of the involved MDR urinary tract bacteria were resistant to quinolones (71.4-76.2% versus 80.3-82%, p > 0.05) and cephalosporins (61.9-81% versus 63.9-83.6%, p > 0.05), both in CoV and non-CoV patients. Conclusions: Patients with urological interventions who remain on indwelling urinary catheters are at an increased risk of developing MDR urinary infections associated with gut microbiota resistant to quinolones and cephalosporins. Patients with MDR UTIs who have CoV-associated symptoms seem to have a higher rate of urosepsis and a longer hospitalization length.